Dampak Media Tanam Dan Pemberian Pupuk NPK Mutiara Terhadap Pertumbuhan Dan Produksi Tanaman Tomat Ceri (lycopersicum esculentum mill.) - Hulu, Aprianus; Zulfida, Ida; Miyarnis, Miyarnis (UNIVERSITAS LABUHANBATU, 2025)
This study aims to investigate the effect of planting media composition and NPK Mutiara fertilizer application on the growth and yield of cherry tomato plants (Lycopersicum esculentum Mill.) in North Sumatra. The research method used a factorial Randomized Block Design (RBD) with two factors: planting media composition (topsoil, cow manure/compost/chicken manure, and rice husk) and NPK Mutiara fertilizer dosage (0, 15, 25, and 35 g/plot). The observed parameters included plant height, number of leaves, number of productive branches, number of fruits per plant, number of fruits per sample, fruit weight per plot, and fruit diameter. The results showed that neither the single effect nor the interaction between planting media and NPK Mutiara fertilizer had a statistically significant effect on the growth and yield of cherry tomatoes. Environmental factors are presumed to be more dominant in influencing the results. Keywords: planting media, NPK fertilizer, growth, yield